Interspecific hybridization improves the performance of Lotus spp. under saline stress. (June 2019) - Escaray, Francisco José; Antonelli, Cristian Javier; Carrasco, Pedro; Ruiz, Oscar Adolfo
Highlights: Accumulation of ions associated to salt conditions differs between tissues and Lotus spp. genotypes. Accumulation of anthocyanins in stems of salt treated Lotus spp. plants is associated to Cl − levels. Interspecific hybridation could provide a tool to obtain cultivars with a high potential to use at saline environments. Abstract: Salinity is one of the most frequent limiting conditions in pasture production for grazing livestock. Legumes, such as Lotus spp. with high forage quality and capable of adapting to different environments, improves pasture performance in restrictive areas. In order to determine potential cultivars with better forage traits, the current study assess the response to salt stress of L. tenuis, L. corniculatus and a novel L. tenuis x L. corniculatus accession. For this purpose, chlorophyll fluorescence, biomass production, ion accumulation and anthocyanins and proanthocyanidins levels have been evaluated in control and salt-treated plants PSII activity was affected by salt in L. tenuis, but not in L. corniculatus or hybrid plants. Analyzed accessions showed similar values of biomass, Na + and K + levels after salt treatment. Increasing Cl − concentrations were observed in all accessions. However, hybrid plants accumulate Cl − in stems at higher levels than their parental. At the same time, the levels of anthocyanins considerably increased in L. tenuis x L. corniculatus stems. Chloride and anthocyanin accumulation in stems could explain the best performance of hybrid plants after a long saline treatment. Finally, as proanthocyanidins levels were no affected by salt, L. tenuis x L. corniculatus plants maintained adequate levels to be used as ruminant feed. In conclusion, these results suggest that hybrid plants have a high potential to be used as forage on salt-affected lands. High Cl − and anthocyanins accumulation in Lotus spp. stems seems to be a trait associated to salinity tolerance, with the possibility of being used in legume breeding programs.